DINAMIKA DAN FAKTOR-FAKTOR PERUBAHAN STRATIFIKASI SOSIAL DI BANTEN - Erlangga Akhazi; Nazwa Azahra, Rusdiyanto, Maftuh Sujana (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This paper investigates the evolving nature of social stratification in Banten, a province with a complex socio-historical background shaped by both traditional hierarchies and contemporary socio-economic forces. Drawing on sociological theories of stratification and social change, this study critically analyzes how structural and cultural transformations have contributed to shifts in class structure, status distribution, and access to resources among different segments of Bantenese society. Historically, social stratification in Banten was deeply influenced by feudal relations, religious authority, and kinship-based systems. However, the past few decades have witnessed significant changes triggered by rapid urbanization, industrial development, educational expansion, and increasing integration with national and global markets. Through qualitative methods—including in-depth interviews with community leaders, historical document analysis, and ethnographic fieldwork—this research identifies several key factors driving these changes: (1) the role of formal education in enabling upward social mobility; (2) the diversification of employment opportunities beyond traditional agrarian sectors; (3) the impact of regional autonomy and democratization in redistributing political power; and (4) the influence of digital media and consumer culture in reshaping social aspirations and identity. Additionally, migration flows and rural-to-urban transitions have reconfigured local social dynamics, generating both opportunities for mobility and new forms of inequality. The findings highlight the multi-dimensional and fluid nature of stratification in contemporary Banten. While traditional markers of status such as lineage and religious prestige persist in certain contexts, they increasingly coexist—and at times compete—with meritocratic and economic indicators of social standing. This research contributes to a broader understanding of how localized processes of stratification are embedded within national development trajectories, and how communities negotiate social change amidst tensions between continuity and transformation